2013
DOI: 10.3989/scimar.03855.28b
|View full text |Cite
|
Sign up to set email alerts
|

Sex ratio estimations of loggerhead marine turtle hatchlings by incubation duration and nest temperature at Sirte beaches (Libya)

Abstract: SUMMARY: Hatchling sex ratios in loggerhead marine turtles (Caretta caretta) were estimated on the beaches near Sirte (Libya), using two methods: incubation duration and nest mean temperature during the middle third of the incubation period. Electronic temperature/humidity loggers were deployed at a total of 13 selected nests at Al-Ghbeba, Al-Thalateen, west of Al-Thalateen, Shash and Al-Arbaeen. The incubation period ranged from 47 to 58 days and average temperature ranged from 29°C to 31.8°C. The maximum tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…In several studies, it was reported that majority of the hatchlings were female due to high nest temperatures. Sex ratios skewed as much as 90% towards females have been found or inferred for loggerhead turtle hatchlings in the USA (Mrosovsky & Provancha 1992;Hanson et al 1998), in Brazil (Marcovaldi et al 1997;Mrosovsky et al 1999) and in the Mediterranean (Kaska et al 1998;Godley et al 2001;Mrosovsky et al 2002;€ Oz et al 2004;Kaska et al 2006;Uçar et al 2012;Jribi et al 2013). Although the majority of the nesting beaches in the world produce highly female-dominated hatchling sex ratios, there are some key sites having conditions that are biased toward producing male hatchlings ) and some small beaches having nearly 1:1 hatchling sex ratios (Mrosovsky et al 1984;Marcovaldi et al 1997;Foley et al 2000;Hawkes et al 2007).…”
Section: Introductionmentioning
confidence: 94%
“…In several studies, it was reported that majority of the hatchlings were female due to high nest temperatures. Sex ratios skewed as much as 90% towards females have been found or inferred for loggerhead turtle hatchlings in the USA (Mrosovsky & Provancha 1992;Hanson et al 1998), in Brazil (Marcovaldi et al 1997;Mrosovsky et al 1999) and in the Mediterranean (Kaska et al 1998;Godley et al 2001;Mrosovsky et al 2002;€ Oz et al 2004;Kaska et al 2006;Uçar et al 2012;Jribi et al 2013). Although the majority of the nesting beaches in the world produce highly female-dominated hatchling sex ratios, there are some key sites having conditions that are biased toward producing male hatchlings ) and some small beaches having nearly 1:1 hatchling sex ratios (Mrosovsky et al 1984;Marcovaldi et al 1997;Foley et al 2000;Hawkes et al 2007).…”
Section: Introductionmentioning
confidence: 94%
“…This study showed that mean temperature in the nest chamber increases 3.2 ºC with respect to the reference sites, and heating was observed in all monitored nests. Yntema and Mrosovsky (1980) stated that a change of 1-2 ºC can make a considerable difference in the sex ratios of hatchlings, and some studies have documented sufficient metabolic heating in nests during TSP to significantly alter the hatchling sex ratios (Broderick et al, 2001;Kaska et al, 2006;Jribi et al, 2013;Tapilatu and Ballamu, 2015;Özdilek et al, 2016). This is because sexual differentiation in sea turtles is strongly influenced by ambient incubation temperature (Standora and Spotila, 1985;Mrosovsky, 1994); more specifically, the embryo is exposed to a continuous temperature during the middle trimester of incubation, which determines the eventual gonadal differentiation and sex of the hatchling (Wibbels, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is less accurate, as it is indirect and based not only on the middle third of the incubation duration when sex is thought to be determined. The other thirds may confound results in case of within clutch heterogeneous temperature regimes [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sex ratio curve (% of females) as a function of incubation duration [ 29 ] was also adapted to the field by adding 4 days, which corresponds to the interval between hatching and the emergence of hatchlings at the sand surface [ 36 ]. The equations of the two curves used (after corrections) calculated by Jribi et al [ 19 ] were used and the exact values of sex ratios were derived.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation